Crosshatch nanofiber networks of tunable interfiber spacing induce plasticity in cell migration and cytoskeletal response. Issue 10 (24th June 2019) - Jana, Aniket; Nookaew, Intawat; Singh, Jugroop; Behkam, Bahareh; Franco, Aime T.; Nain, Amrinder S.
ABSTRACT: Biomechanical cues within tissue microenvironments are critical for maintaining homeostasis, and their disruption can contribute to malignant transformation and metastasis. Once transformed, metastatic cancer cells can migrate persistently by adapting (plasticity) to changes in the local fibrous extracellular matrix, and current strategies to recapitulate persistent migration rely exclusively on the use of aligned geometries. Here, the controlled interfiber spacing in suspended Crosshatch networks of nanofibers induces cells to exhibit plasticity in migratory behavior (persistent and random) and the associated cytoskeletal arrangement. At dense spacing (3 and 6 µm), unexpectedly, elongated cells migrate persistently (in 1 dimension) at high speeds in 3‐dimensional shapes with thick nuclei, and short focal adhesion cluster (FAC) lengths. With increased spacing (18 and 36 µm), cells attain 2‐dimensional morphologies, have flattened nuclei and longer FACs, and migrate randomly by rapidly detaching their trailing edges that strain the nuclei by ∼35%. At 54‐µm spacing, kite‐shaped cells become near stationary. Poorly developed filamentous actin stress fibers are found only in cells on 3‐µm networks. Gene‐expression profiling shows a decrease in transcriptional potential and a differential up‐regulation of metabolic pathways. The consistency in observed phenotypes across cell lines supports using this platform to dissect hallmarks of plasticity in migration in vitro .—Jana, A., Nookaew, I., Singh, J., Behkam, B., Franco, A. T., Nain, A. S. Crosshatch nanofiber networks of tunable interfiber spacing induce plasticity in cell migration and cytoskeletal response. FA8EB J. 33, 10618–10632 (2019). www.fasebj.org